2020
DOI: 10.1302/0301-620x.102b11.bjj-2020-0284.r1
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict outcome after treatment of long bone osteomyelitis?

Abstract: Aims This study presents patient-reported quality of life (QoL) over the first year following surgical debridement of long bone osteomyelitis. It assesses the bone involvement, antimicrobial options, coverage of soft tissues, and host status (BACH) classification as a prognostic tool and its ability to stratify cases into ‘uncomplicated’ or ‘complex’. Methods Patients with long-bone osteomyelitis were identified prospectively between June 2010 and October 2015. All patients underwent surgical debridement in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…As a classification system, it is a useful guide for predicting outcomes. Osteomyelitis classified as ‘uncomplicated’ is a good prognostic indicator for improved quality of life following intervention ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a classification system, it is a useful guide for predicting outcomes. Osteomyelitis classified as ‘uncomplicated’ is a good prognostic indicator for improved quality of life following intervention ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amputation is frequently utilised as a surrogate for poor outcome or treatment failure; however, there is an increasing body of literature supporting early amputation under circumstances, where the outcome is likely to be poor, or the morbidity of treatment high. Multiple studies in trauma have demonstrated that early amputation results in fewer overall complications, more rapid resolution of symptoms and equivalent or superior functional outcomes to those undergoing limb reconstruction techniques [44][45][46][47]. It is important, therefore, that the concept of functional amputation, where this approach is considered as a treatment choice rather than a last resort, is developed and discussed with patients at an early stage.…”
Section: Amputationmentioning
confidence: 99%
“…In 2018, organizations including the European Bone and Joint Infection Society and the Association for the Study of Internal Fixation worked together to develop a consensus on FRI to standardize the clinical reports and improve the quality of published literature ( Metsemakers et al, 2018 ; Govaert et al, 2020 ). Despite advances in the treatment of FRI, the diagnosis and treatment of FRI are still in the process of continuous exploration due to its diversity and complexity ( Foster et al, 2020 ; Hak, 2020 ; Hotchen et al, 2020 ; Metsemakers et al, 2020 ). Understanding the epidemiology and risk factors for FRI may lead to better prevention and treatment methods in the future.…”
Section: Introductionmentioning
confidence: 99%